The Growth of Sharia Insurance in Indonesia 2015 – 2016: an Academic Forecast Analysis - Muthmainah, Muthmainah (Shirkah: Journal of Economics and Business, 2016)
This research is intended to analyze and to forecast the growth of sharia insurance in Indonesia, using Autoregressive Integrated Moving Average (ARIMA) analysis. The variables used in this research are assets, investments, premium, and claims. Quarterly time series data from period quarter I (March 2015) up to quarter IV (December 2016), gathered from Islamic Insurance Statistic Published by Otoritas Jasa Keuangan (OJK), are being carefully examined and academically predicted. As a result, ARIMA analysis show that the growth of sharia insurance in Indonesia has fluctuated, confidently it can be predicted that nominally it will increase in each quarter, including its’ assets, investments, premium and claims.  This research would especially contribute to the sharia insurance companies to formulate their strategies in the future.  Keywords: sharia insurance, ARIMA, islamic insurance statistic